Leadership Style, Work Environment, and Work Communication as Determinants of Generation Z Employee Performance at PT. Semoga Berkah Sukses - Putri, Pingkan Novita Yanda; Ubaidillah, Hasan; Abadiyah, Rifdah (PT Keberlanjutan Strategis Indonesia, 2026)
The point of this study is to look into how leadership style, work setting, and communication at work affect the success of Generation Z workers. In this study, leadership style, work setting, and communication at work are the independent factors. Employee success is the dependent variable. The study uses a descriptive quantitative method, which means that the numbers from the research results are used to explain things. The people in this study are all Generation Z workers at PT Semoga Berkah Sukses; there are 100 of them. The total sampling method was used to get a group that was representative of the whole population so that the results could be used more widely. For this study, version 25 of the SmartPLS (Partial Least Squares Structural Equation Modeling) program was used to help look at the data.